Tinjauan Pemanfaatan Hutan Pinus di Kabupaten Gayo Lues Berdasarkan UU No.41 Tahun 1999 Tentang Kehutanan - Citra Perdana Kesuma (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Article 33, Paraghraph 3 of the Constitution of the Republic of Indonesia clearly states that the lard, water and natural resources contained therein are controlled by the state and utilized for the greatest property of the people. Forest, as a gift from God Almighty are a blessing bestowed upom the Indonesia Nation. These forest are involable natural resources that must be apraciated and manage responsibly. Forest managament is viewed as direct manded that requirest the forest to be utilized while considering the local wisdom of the communities, reflecting gratitude to God Almighty. The utilization of forests as capital of national development provides tangible benefit for the lives and livelihoodes of the indonesion people, including ecological, socio-cultural, and economic benefit in a balance and dynamic manner. Forest must be administered, managed, protected,and sustainbly, utilized for the welfare of the Indonesian people bot current and future generation. Aceh is a spesial region with spesific regulation trough the Aceh Government Law, allowing it to implement unique policies within its teritori, including those releted to forestry. In Gayo Lues, region with substantial forested areas, pine tree taping activities are conducted by both companies with government permits and local communities based on their land ownership claims as recognized by local knowledge.